2011
DOI: 10.1002/cbdv.201000163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vitro Activity of Dermaseptin 01, a Cationic Antimicrobial Peptide, against Schistosoma mansoni

Abstract: Schistosomiasis is a neglected tropical disease that remains a considerable public health problem worldwide. Since the mainstay of schistosomiasis control is chemotherapy with a single drug, praziquantel, drug resistance is a concern. Here, we examined the in vitro effects of dermaseptin 01 (DS 01), an antimicrobial peptide found in the skin secretion of frogs of the genus Phyllomedusa, on Schistosoma mansoni adult worms. DS 01 at a concentration of 100 μg/ml reduced the worm motor activity and caused the deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 55 publications
12
39
0
Order By: Relevance
“…Similar results were obtained by previous studies using other antischistosomal compounds, such as piplartine, dermaseptin and phytol de Moraes et al, 2011;de Moraes et al, 2014). The schistosomes tegument is an important target for antischistosomal drugs, alterations in the surface topography of worms were used by several studies for the evaluation of antischistosomal drugs activities in vitro and in vivo (Veras et al, 2012;Guimarães et al, 2014;de Moraes et al, 2014).…”
Section: Effect Of Neem Ee On S Mansonisupporting
confidence: 83%
“…Similar results were obtained by previous studies using other antischistosomal compounds, such as piplartine, dermaseptin and phytol de Moraes et al, 2011;de Moraes et al, 2014). The schistosomes tegument is an important target for antischistosomal drugs, alterations in the surface topography of worms were used by several studies for the evaluation of antischistosomal drugs activities in vitro and in vivo (Veras et al, 2012;Guimarães et al, 2014;de Moraes et al, 2014).…”
Section: Effect Of Neem Ee On S Mansonisupporting
confidence: 83%
“…In this context, alterations of the tegument of S. mansoni induced by several antischistosomal compounds have also been described (25)(26)(27)(28)(29). In this study, we observed extensive tegumental damage in S. mansoni that intensified progressively when the concentrations of the oxindolimine-metal complexes tested increased.…”
supporting
confidence: 71%
“…All the experiments were performed in triplicate and were repeated at least three times. The parasites were maintained for 120 h and monitored every 24 h using a light microscope to evaluate their general condition: motor activity and mortality rate [11,12].…”
Section: In Vitro Studies Of Adult Schistosomes and Assessment Of Drumentioning
confidence: 99%